Protocol for a feasibility trial to inform the development of a breathlessness rehabilitation programme for chronic obstructive pulmonary disease and chronic heart failure (the COHERE trial) - Sally J Singh; Rachael A Evans; Amy V Jones; Dale W Esliger; Lauren B Sherar (BMJ Open, 2019)
Introduction Adults with chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF) commonly suffer from exertional dyspnoea and fatigue. Exercise training is recommended in the management of both diseases, yet many of the outcome measures traditionally reported are disease specific and may not fully acknowledge the multimorbid older adult. Based on our previous research, a breathlessness rehabilitation programme for patients with COPD/CHF or combined disease has been introduced as a service improvement within University Hospital Leicester National Health Service Trust and has amalgamated aspects of cardiac and pulmonary rehabilitation. This has created an opportunity to expand the outcome measures assessed and introduce a holistic approach in a population that share common symptoms. Therefore, this multisite trial will explore the feasibility of collecting novel outcome markers as part of a comprehensive assessment prior to enrolment in a breathlessness rehabilitation programme for participants with COPD and/or CHF.Methods and analysis The rehabilitation programme consists of 12 sessions, twice weekly, over a 6-week period. In addition to usual rehabilitation outcome measures, the trial will collect measures of future cardiometabolic risk including arterial stiffness, body composition, physical activity/sedentary time, frailty and symptom burden in a comprehensive rehabilitation assessment. The primary outcome measures will centre around feasibility (eg, acceptability of the comprehensive rehabilitation assessment, intervention delivery and the experiences and attitudes of healthcare professionals and participants). Focus groups and interviews will be conducted to further explore barriers and facilitators to the operation and participation in a breathlessness rehabilitation programme and the trial. Thematic analysis will be used for the interpretation of all qualitative data.Ethics and dissemination The research ethics committee East Midlands Leicester-Central has provided ethical approval for the conduct of this trial. The results of the trial will be disseminated through appropriate conference proceedings and peer-reviewed journals.Trial registration number ISRCTN11636308